Espalhamento de pacotes de ondas em canais quânticos formados por semicondutores porosos - Lopes, Daniel Suárez (2023)
Disorder in experimentally two-dimensional (2D) heterostructured semiconductor materials is inevitable, which can originate from charged impurities, vacancies or atomic substitution. Numerous exciting phenomena arise in disordered quantum materials, such as, for example, the metal-insulator transition, which can be explained by the Anderson localization effect. For transport properties, a 2D system described by a disordered potential can exhibit diffusion-ballistics and localization-dislocation transitions by decreasing (holding fixed) the size of the system for a fixed (increasing) disorder. The presence of porosities in semiconductor materials, called porous materials, can be used to propose new devices for applications, such as, for example, waveguides. For the study of the electronic states for a porous quantum system (well), made of InAlAs/InGaAs, it is necessary the quantitative solution of the Schrödinger transmission independent of time in the approximation of the effective mass with the finite difference technique. In the context of electronic transport properties and porous materials, a suitable theoretical and didactic description is based on wave packet capacity. Thus, we investigate the dynamics of the wave packet propagating through a porous semiconductor channel with the defects being simulated by a disordered scattering region produced by monitoring potential. The theoretical framework is based on the split-operator technique to solve the time-dependent Schrödinger pass within the effective mass approximation. In the simulation, consider the semiconductor channel made by InGaAs with a width of 100 Å, grown on InAlAs substrates, and the porous ones are taken with circular symmetry and different densities. The results for the probability, reflection and current transmission coefficients are analyzed for different: initial values of kinetic energy of the Gaussian wave packet, disordered pore densities and pore randomness. It is shown that the inter-subband transitions are strongly dependent on the configuration of the disordered scattering region.